Enzymatic Fibre Modification During Production of Dissolving Wood Pulp for Regenerated Cellulosic Materials - Loureiro, Pedro E. G.; Cadete, Sonia M. S.; Tokin, Radina; Evtuguin, Dmitry V.; Lund, Henrik; Johansen, Katja S. (Frontiers in Plant Science, 2021)
The production of regenerated cellulosic fibres such as viscose, modal and lyocell, is based mainly on the use of dissolving wood pulp as raw material. Enzymatic processes are an excellent alternative to conventional chemical routes in the production of dissolving pulp, in terms of energy efficiency, reagent consumption and pulp yield. The two main characteristics of a dissolving pulp are the cellulose purity and the molecular weight, both of which can be controlled with the aid of enzymes. A purification process for paper-grade kraft pulp has been proposed, based on the use of xylanases in combination with cold caustic extraction, without the conventional prehydrolysis step before kraft pulping. Endoglucanases can efficiently reduce the average molecular weight of the cellulose while simultaneously increasing the pulp reactivity for viscose production. It is shown in this study, for the first time, that lytic polysaccharide monooxygenases act synergistically with endoglucanases in the modification of bleached dissolving pulp.